The neighborhood food environment modifies the effect of the 2009 WIC food package change on childhood obesity in Los Angeles County, California - Christopher E. Anderson; Catherine M. Crespi; May C. Wang; Shannon E. Whaley; M. Pia Chaparro (BMC, 2020)
Abstract Background Food packages provided by the Special Supplemental Nutrition Program for Women, Infants and Children (WIC) were revised in 2009 to better align them with the Dietary Guidelines for Americans. This study was conducted to evaluate whether the effect of the food package change on childhood obesity varied by the food environment in the neighborhoods where WIC-participating children live. Methods Administrative data from participating children in Los Angeles County, California (2003-2016) were merged with geocoded food vendor information by neighborhood of residence. Obesity risk at age 4 was compared between children receiving old (2003-2009) and new (2010-2016) WIC food packages using sex-stratified Poisson regression models, with interaction terms between WIC package and neighborhood density (number per square mile) of healthy and unhealthy food outlets. Results The new food package was associated with a significant decrease in obesity risk. Among boys, the new food package was associated with 8 to 18% lower obesity risk at all healthy and unhealthy food outlet densities, and the association was not modified by neighborhood food outlet density. Among girls, the association of the new food package with obesity risk was protective in neighborhoods with high healthy and low unhealthy food outlet densities, and adverse in neighborhoods with high unhealthy and low healthy food outlet densities. The effect of the new food package among girls was modified by unhealthy food outlet density, with significantly smaller (p-value = 0.004) decreases in obesity risk observed in neighborhoods with higher unhealthy food outlet density. Conclusions The impact of the food package change was modified by the neighborhood food environment among girls only. Future policy changes should incorporate consideration of ways to mitigate potentially inequitable geographic distribution of the health benefits of policy changes.